Advanced nutrition and dietetics in obesity - Hankey, Catherine; Whelan, Kevi (Advanced nutrition and dietetics, 2018)
"This addition to the British Dietetic Association Advanced Nutrition and Dietetics book series is written for clinicians and researchers who work with any aspect of obesity and its comorbid conditions. Featuring contributions from leading researchers and practitioners from around the globe Advanced Nutrition and Dietetics in Obesity offers a uniquely international perspective on what has become a worldwide public health crisis"--Provided by publisher.